The peri-operative pain management of total abdominal hysterectomy patients at an academic hospital - Dougall, Lauren Dawn (Department of Anaesthesia and Perioperative Medicine, 2019)
This study was undertaken to assess the performance of the peri-operative pain management and describe the patient satisfaction following elective total abdominal hysterectomy cases at Rahima Moosa Mother and Child Hospital in Johannesburg, South Africa. The data obtained were collected utilising the questionnaire of the international pain registry PAIN-OUT, to allow for a standardised means of assessment and follow-up. All patients who presented for this procedure during a three-month period from September to November 2015 were approached on the first post-operative day. Patient demographics and details regarding the peri-operative interventions were collected from patient charts and a self-reported patient questionnaire was completed. The data obtained examined the personal pain experience as well as resultant functional limitations and emotional factors involved. Medication side-effects, patient opinions regarding appropriateness of their pain management, their degree of participation, whether information was offered to them and their overall satisfaction levels with care was sought. The study included 76 patients and highlighted unacceptable acute pain levels. It revealed deficiencies in administration of analgesics on the ward and a lack of standardised protocols or collaboration between Anaesthesiology and Gynaecology in managing acute postoperative pain. Patients were not uniformly advised regarding the post-operative expectations of their pain and non-pharmacological measures were not emphasised by the treating team. Despite these deficiencies, patients reported high levels of satisfaction with the care received. The information provided allows for a more focused quality improvement strategy to manage acute post-operative pain in this group more effectively and move toward better collaboration between departments involved in the care of patients peri-operatively.